Efgartigimod as a fast-acting treatment in generalized very-late-onset myasthenia gravis - Zhang, Zhouao; Yang, Mingjin; Guo, Xinyan; Ma, Tianyu; Wang, Zhouyi; Luo, Tiancheng; Peng, Deyou; Du, Xue; Huang, Xiaoyu; Zhang, Yong (Frontiers in Immunology, 2025)
ObjectiveEfgartigimod (EFG), a neonatal Fc receptor antagonist that facilitates the degradation of pathogenic immunoglobulin G, is approved for the treatment of generalized myasthenia gravis (MG). This study aims to evaluate the efficacy and safety of EFG in patients with very-late-onset myasthenia gravis (VLOMG).MethodsThis study enrolled 15 consecutive patients diagnosed with VLOMG who received EFG treatment. Baseline demographic and clinical characteristics, as well as dynamic changes in the MG-specific activities of daily living (MG-ADL) score and quantitative MG (QMG) score, were systematically recorded.ResultsPatients were stratified into two groups: a worse group (n = 8) and a new-diagnosed group (n = 7), the latter of which included 5 patients who had received monotherapy with pyridostigmine (Py) prior to EFG. At week 5, the mean changes in MG-ADL scores were -4.9 ± 3.3 in the overall VLOMG cohort, -6.1 ± 3.1 in the new-diagnosed group, -6.6 ± 3.6 in the mono-Py subgroup, and -3.8 ± 3.2 in the worse group. The clinical meaningful improvement (CMI) rate was 86.7% (13/15) in the overall cohort, 75.0% (6/8) in the worse group, and 100.0% (7/7) in the new-diagnosed group. During a mean follow-up time of 39.2 ± 16.2 weeks, symptoms remained stable in responsive patients, with various treatment strategies implemented following the fast-acting treatment of EFG. No adverse drug reactions were reported in this cohort.ConclusionThis study demonstrates that EFG is an effective and safe treatment for patients with VLOMG. EFG exhibits potential as an early, fast-acting treatment and may confer sustained clinical benefits in this patient population.